Pengaruh Terapi Musik Klasik Morning Mood terhadap Tingkat Stress pada Penderita Hipertensi di Rw 005 Sawangan Baru Tahun 2023 - Ath Thaariq Wal Ramadhan; Ns. Ahmad Rizal; Ns. Elvie Tresya (Inovasi Kesehatan Global, 2024)
Hypertension is a state of high blood pressure when at rest the systolic blood pressure is 140 mmHg and above or the diastolic blood pressure is 90 mmHg and above after repeated measurements. Because hypertension has several causes, one of which is age. An elderly person is someone who is 60 years old, where the individual has experienced the aging or aging process. When you get older, the most common thing that happens is stress. Stress is a condition produced by environmental changes that are perceived as challenging, threatening or damaging to a person's balance or dynamic state. Because music is a rhythm that can bring an atmosphere and it is believed that music can calm the mind, especially classical music, and the effect of classical music can reduce stress. This study aims to determine the effect of classical music therapy on changes in stress levels in elderly people with hypertension in the Rw 005 Sawangan Baru area in 2023. The population in this study was 30 elderly people, and with a sample of 15 respondents. This research design uses pre-experimental with a one group pretest posttest design approach. The way to collect data is to use the Depression Anxiety Stress Scales (DASS 42) questionnaire as a tool to measure stress levels. The results of the research showed that the average blood pressure before classical music therapy was 160/100 MmHg, then after classical music therapy it was found to be 130/80 MmHg, meanwhile the stress level in the elderly before and after classical music therapy morning mood was the same as The average P - value or sig value is 0.000, which means less than p <0.05 by using the Paired Simple T-Test statistical test and stating that the hypothesis Ha (Alternative Hypothesis) is accepted and Ho (Null Hypothesis) is rejected by getting a significant change in before and after giving classical music therapy. It can be concluded that there is an influence of classical music therapy on stress levels in elderly people with hypertension.